Trends in airport surface access in the London multi-airport system - Moxon, Richard (Hellenic Aviation Society, 2016)
The London multi-airport system is described and changes in ownership from state organisations to competing private enterprises are assessed. A taxonomy of United Kingdom government action related to airport planning policy is presented with critical analysis in relation to airport surface access strategy. Changes in public transport use by passengers and employees at London airports are quantified to illustrate the success or otherwise of government policy. Passenger groups (defined by nationality and trip purpose) driving the increase in public transport are identified. Current London airport surface access strategic targets for passengers and employees are compared with the early versions suggested by the government to highlight the changed airport approach. Emerging surface airport access issues at London’s airports are discussed.
Keywords: United Kingdom airport policy; Airport surface access strategy; Multi-airport systems; Airport planning